The true story of Alice B. Toklas : a study of three autobiographies - Linzie, Anna, 1971- (University of Iowa Press, 2006)
In this original and intriguing study, Anna Linzie examines three mid-twentieth-century texts never before treated as interrelated in a book-length work of literary criticism: Gertrude Stein's The Autobiography of Alice B. Toklas (1933) and Alice B. Toklas's The Alice B. Toklas Cook Book (1954) and What Is Remembered (1963). Taking these three texts as intertexts or as an assemblage of the true story of Alice B. Toklas, Linzie challenges assumptions about primary authorship and singular identity that have continued to limit lesbian and feminist rereadings of autobiography as a genre and of Ste.